An experimental evaluation on the utility of burglary profiles applied in active police investigations - Fox, Bryanna (Criminal justice and behavior, 2015)
This study evaluated the effect on burglary arrest rates when using statistically derived behavioral profiles for burglary offenses and offenders in active police investigations. To do this, an experiment was conducted where one police agency that used the profiles was compared with three matched police agencies that did not. Burglary arrest rates were studied 4 years before and 1 year after the profile was implemented. Results show that the arrest rates for the treated agency increased by 3 times as compared with the control agencies. The interaction effect between treatment/control agency and pretest/posttest arrest rates was significant, showing that the experimental intervention had an effect, after controlling for pre-existing differences between the agencies. These findings on the utility of offender profiling, the first to be derived from an experiment conducted in active police investigations, suggest that the statistically based behavioral profiles could be a useful tool in increasing arrest rates for police.